Malnutrition and female political representation in India - Parul Tyagi; Philippe LeMay-Boucher (PLoS ONE, 2026)
Malnutrition casts a negative shadow over the course of the lives of a fifth of children under the age of five who are stunted worldwide. Despite two decades of growth, India has one of the highest wasting and stunting rates. Lack of political awareness and poor governance, arguably related to an acute underrepresentation of women in politics in India may explain why not enough is committed to this matter. Increasing women’s political agency in elected bodies has brought several documented benefits yet little is known about its impact on children’s nutrition outcomes. Our analysis shows that increasing women’s political representation in India’s state legislatures could reduce child malnutrition. We use a large cross-sectional district representative household survey collected between 2002−4 through the second round of the District Level Household Survey. It is merged with detailed state legislative assembly election data we collected. These detail who contested seats in each constituency and the gender composition of elected representatives in India’s 17 largest states between 1993 and 2004. We find that a ten-percentage point increase in women’s representation leads to a three to five percentage point reduction in the likelihood of a child being underweight. Malnutrition is a multi-faceted issue with different underlying causes, and our work explores some of these. We document that greater female political representation creates productive ways to enhance public health by bringing improvements in households’ access to basic amenities and to prenatal, birth and postnatal care among mothers.